Does early detection of otitis media with effusion prevent delayed language development?. Issue 2 (1st August 2001) - Butler, C C; MacMillan, H
Abstract : OBJECTIVE: To consider whether earlier detection of otitis media with effusion (OME) in asymptomatic children in the first 4 years of life prevents delayed language development. METHODS: MEDLINE and other databases were searched and relevant references from articles reviewed. Critical appraisal and consensus development were in accordance with the methods of the Canadian Task Force on Preventive Health Care. RESULTS: No randomised controlled trials assessing the overall screening for OME and early intervention to prevent delay in acquiring language were identified, although one trial evaluated treatment in a screened population and found no benefit. The "analytic pathway" approach was therefore used, where evidence is evaluated for individual steps in a screening process. The evidence supporting the use of tools for early detection such as tympanometry, microtympanometry, acoustic reflectometry, and pneumatic otoscopy in the first 4 years of life is unclear. Some treatments (mucolytics, antibiotics, steroids) resulted in the short term resolution of effusions as measured by tympanometry. Ventilation tubes resolved effusions and improved hearing. Ventilation tubes in children with hearing loss associated with OME benefited children in the short term, but after 18 months there was no difference in comparison with those assigned to watchful waiting. Most prospective cohort studies that evaluated the association between OME and language development lacked adequate measurement of exposure or outcome, or suffered from attrition bias. Findings with regard to the association were inconsistent. CONCLUSIONS: There is insufficient evidence to support attempts at early detection of OME in the first 4 years of life in the asymptomatic child to prevent delayed language development.